Psycholinguistic skills and school performance - Núñez Grandón, Alejandro; Pérez Serey, Jazmín (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The objective of this study is to determine the relationship between psycholinguistic skills and school performance. The present study is quantitative, descriptive correlational, non-experimental cross-sectional. The sample consisted of 35 4th year students from a subsidized private school in Chillán, Chile. Data collection was obtained through the application of the Illinois Test of Psycholinguistic Aptitudes and the final average of the subjects of Language, Mathematics, Social Sciences and History and Geography. Through this research, it is concluded that a partial relationship between Psycholinguistic Skills and Academic Performance is established.